EVALUASI KEPEMIMPINAN PEMBELAJARAN GURU PENGGERAK DI SMAN 1 LINTAU BUO KABUPATEN TANAH DATAR - muharnis; Asmendri; Yusuf Salam, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to evaluate and analyze the instructional leadership of leading teachers before and after participating in the Leading Teacher Education Program. This study used a mixed methods research with a concurrent embedded model. The results showed that based on the perspectives of students, colleagues, according to the Principal, according to the leading teachers themselves, the leadership value after the program was in the very high category. This data was supported by the results of observations that showed an increase in the leading teachers' sensitivity to student needs, the implementation of enjoyable learning, increased self-reflection, and strengthened collaboration with fellow teachers. Leading teachers were also more active in leading the learning process, actively involving students, improving decision-making skills, and playing a strategic role in building a positive learning culture in the school.